2001
DOI: 10.1117/1.1413209
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the contributions of NADH and collagen to cervical tissue fluorescence spectra: Modeling, measurements, and implications

Abstract: Monte Carlo techniques provide an important means to investigate the combined contributions of multiple fluorophores to measured emission spectra. The approach will prove increasingly valuable as a more sophisticated understanding of in vivo optical properties is developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
202
0
4

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 268 publications
(215 citation statements)
references
References 27 publications
9
202
0
4
Order By: Relevance
“…The axial and radial grid sizes were set at 5 μm, and the numbers of axial and radial grids were set at 900 and 50, respectively to define the region of interest within the epithelial tissue model. Fluorescence was simulated in the homogeneous medium for two different sets of optical properties, which correspond to those of the epithelial and stromal layers in epithelial tissues at an excitation-emission wavelength pair of 410-460 nm ( Table 2, set 1) and were obtained from the publication by Drezek et al (32). Optical properties at 410-460 nm were used because fluorescence spectra at an excitation wavelength of 410 nm (measured with the unshielded probe geometry) were found to be most useful for the diagnosis of dysplasia (see Results section).…”
Section: Monte Carlo Simulationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The axial and radial grid sizes were set at 5 μm, and the numbers of axial and radial grids were set at 900 and 50, respectively to define the region of interest within the epithelial tissue model. Fluorescence was simulated in the homogeneous medium for two different sets of optical properties, which correspond to those of the epithelial and stromal layers in epithelial tissues at an excitation-emission wavelength pair of 410-460 nm ( Table 2, set 1) and were obtained from the publication by Drezek et al (32). Optical properties at 410-460 nm were used because fluorescence spectra at an excitation wavelength of 410 nm (measured with the unshielded probe geometry) were found to be most useful for the diagnosis of dysplasia (see Results section).…”
Section: Monte Carlo Simulationsmentioning
confidence: 99%
“…The thickness of the epithelial layer and that of the stromal layer were fixed at 450 μm and 2050 μm, respectively. A thickness of 450 μm was chosen for the epithelial layer to approximate the average thickness of the normal human cervical epithelium (4,6,8,32). The thickness of the stromal layer was set at 2050 μm to represent an infinitely thick tissue.…”
Section: Monte Carlo Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluorescence spectroscopy has high diagnostic accuracy when the results of NADH and collagen fluorescence are considered together with only 4.34 % false negative. However, false positive could not be calculated due to lack of control a False positive rates could not be calculated in the case of fluorescence spectroscopy as tissue from normal subjects could not be studied which is non-fluorescent [6]. In this study, significant epithelial fluorescence was observed in most of the fresh tissue sections and the fluorescence intensity increased at 460 nm excitation in dysplastic samples relative to normal samples from the same patient.…”
Section: Discussionmentioning
confidence: 79%
“…Keratin and Elastin molecules of connective tissue emit auto fluorescent light at 430 nm. Both molecules are rare in intervertebral discs and do not contribute to disc auto florescence [2,5,8,9] All collagen molecules in all tissues emit auto fluorescent light under UV irradiation [7,13,20,25]. Other molecules-particularly hemoglobin-extinct the auto fluorescence [12].…”
Section: The Origin Of Auto Fluorescencementioning
confidence: 99%